Addition of a combination of creatine, carnitine, and choline to a commercial diet increases postprandial plasma creatine and creatinine concentrations in adult dogs - Banton, Sydney; Braun, Ulrike; Squires, E. James; Shoveller, Anna K. (Frontiers in Veterinary Science, 2022)
Creatine is a nitrogenous compound essential for cellular energy homeostasis found in animal protein; however, when heat-processed for pet food, creatine is degraded to creatinine, which is not metabolically active and excreted in urine. The objective of the present investigation was to define the postprandial plasma creatine and creatinine response in dogs fed a commercial diet (CON) formulated for adult dogs, top-dressed with a combination of creatine (9.6 g/kg dry matter, DM), carnitine (2.13 g/kg DM) and choline (0.24 g/kg DM; CCC), methionine (2.6 g/kg DM; MET) or taurine (0.7g/kg DM; TAU). Eight adult Beagles were fed one of the four diets for 7 days in a Latin Square design with no washout period. On day 7, cephalic catheters were placed and blood samples were collected before being fed (fasted) and up to 6 hours post-meal. Creatine and creatinine were analyzed using HPLC and data analyzed using PROC GLIMMIX in SAS. Plasma creatine concentrations were higher in dogs fed CCC (103±10 µmol/L) compared to MET (72±7 µmol/L) at fasted (P<0.05) and higher compared to all other treatments from 15 to 360 minutes post-meal (P<0.05). Plasma creatinine concentrations were higher in dogs fed CCC from 60 to 180 min compared to all other treatments. These data suggest that when creatine, carnitine and choline are top-dressed for 7 days, plasma creatine is rapidly absorbed and remains elevated up to 6 hours post-meal. This may have implications for energy metabolism and should be considered when using creatinine as a diagnostic tool in dogs.